Ketahanan Keluarga Fatherless Dan Dampaknya Terhadap Kesiapan Anak Perempuan Menikah: Studi Kasus di Kecamatan Wiradesa Kabupaten Pekalongan - muhlisin, imam; Umardani, Achmad (Al-Hukkam: Journal of Islamic Family Law, 2025)
The phenomenon of fatherlessness in the family has a significant impact on family resilience and daughters' readiness to marry. This study aims to examine the resilience of fatherless families in Wiradesa District, Pekalongan Regency and analyze its impact on daughters' readiness to face marriage. The research method uses qualitative recearch with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that families with fatherless conditions in this area continue to try to maintain family resilience despite experiencing various emotional and social challenges. The absence of a father (fatherless) significantly affects the thoughts, feelings, and behaviors of daughters in preparing and motivating them to marry. This indicates that the fatherless phenomenon can lead to social psychological disturbances in daughters in the Wiradesa sub-district.. This study emphasizes the importance of the role of fathers in shaping daughters' emotional readiness to undergo marriage and recommends the need to strengthen social support and family education programs to overcome the impact of fatherlessness